MULTIDIMENSIONAL APPROACH TO PATIENT SATISFACTION IN HEMODIALYSIS NURSING SERVICES AT ROYAL PRIMA GENERAL HOSPITAL, MEDAN - Evalatifah Nurhayati; Elis Anggeria; Tiarnida Nababan (Universitas Nahdlatul Ulama Surabaya, 2026)
Background: The increasing population of patients with end-stage kidney disease necessitates high-quality nursing services. Patient satisfaction in hemodialysis is a multidimensional construct encompassing physical, psychological, and technical aspects of care. Objective: To analyze patient satisfaction through a multidimensional approach and identify the dominant factor influencing satisfaction at Royal Prima General Hospital, Medan, in 2025.Methods: This quantitative study used a cross-sectional design. Total sampling was applied to 115 hemodialysis patients (Sample). Variables included nine dimensions of service measured via a multidimensional questionnaire (Instrument). Data were analyzed using univariate, bivariate (Chi-square), and multivariate (Logistic Regression) tests (Analysis).Results: Patients reported high satisfaction levels, categorized as very satisfied (52.5%) and satisfied (47.5%). All service dimensions significantly correlated with satisfaction (p≤ 0.05). Multivariate analysis identified medical care as the most dominant factor (p = 0.000; B = 0.104), indicating its critical role in shaping patient perceptions.Conclusion: Nursing service quality across multiple dimensions significantly drives patient satisfaction, with medical care being the most influential. Hospitals should focus on enhancing medical care, nurse responsiveness, and therapeutic communication to sustain service quality.